Novel 1, 3, 4‐Oxadiazole Derivatives of Dihydropyrimidinones: Synthesis, Anti‐Inflammatory, Anthelmintic, and Antibacterial Activity Evaluation. (14th July 2015) - Shaikh, Ambareen; Meshram, Jyotsna
Abstract : The present study depicts synthesis of a series of some novel 5‐(5‐(aryl)‐1, 3, 4‐oxadiazol‐2‐yl)‐3, 4‐dihydro‐6‐methyl‐4‐styrylpyrimidin‐2(1H)‐one derivatives. All the newly synthesized compounds were characterized by FTIR, 1 H NMR, 13 C NMR, mass spectrometry, and elemental analysis. The compounds were evaluated for their in vivo anti‐inflammatory activity by the carrageenan‐induced rat paw edema method. The compounds were also screened for their anthelmintic activity on Indian earthworms andantibacterial activity against some gram positive and gram negative strains of bacteria. This pharmacological activity evaluation revealed that, among all the compounds screened, compounds4b and4c were found to have promising anti‐inflammatory activity. Interestingly, compounds4b, 4c, and4i exhibited appreciable anthelmintic property, while compounds4c, 4g, and4h showed leadingantibacterial activity against the selected pathogenic strains of bacteria. Abstract :